College Algebra (6th Edition)

Published by Pearson
ISBN 10: 0-32178-228-3
ISBN 13: 978-0-32178-228-1

Chapter 2 - Functions and Graphs - Exercise Set 2.2: 69

Answer

The difference quotient for the given function is $-4x-2h-1$

Work Step by Step

$f(x)=-2x^{2}-x+3$ Find the difference quotient $\dfrac{f(x+h)-f(x)}{h}$ Start by finding $f(x+h)$. Substitute $x$ by $x+h$ in $f(x)$ and simplify: $f(x+h)=-2(x+h)^{2}-(x+h)+3=...$ $...=-2(x^{2}+2xh+h^{2})-x-h+3=...$ $...=-2x^{2}-4xh-2h^{2}-x-h+3$ Substitute the known values into the formula for the difference quotient: $\dfrac{f(x+h)-f(x)}{h}=...$ $...=\dfrac{-2x^{2}-4xh-2h^{2}-x-h+3-(-2x^{2}-x+3)}{h}=...$ $...=\dfrac{-2x^{2}-4xh-2h^{2}-x-h+3+2x^{2}+x-3}{h}=...$ $...=\dfrac{-4xh-2h^{2}-h}{h}=...$ Take out common factor $h$ from the numerator and simplify:" $...=\dfrac{h(-4x-2h-1)}{h}=-4x-2h-1$ The difference quotient for the given function is $-4x-2h-1$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.